ANALISIS KOMPETENSI GURU DALAM PELAKSANAAN PEMBELAJARAN K13 PADA TEMA 1 SUBTEMA 3 KELAS IV SDN 181 PEKANBARU - Wiwit Yuninda; Lazim N (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research is motivated by the differences in the implementation of 2013 curriculum learning with the previous curriculum. This study aims to describe the competence of teachers in the implementation of K13 learning on the theme 1 sub-theme 3 of class IV SDN 181 Pekanbaru, and the subjects in this study were IVB class teachers. The research design in this study is descriptive qualitative. Data collection is done by observation, interviews and documentation. Data analysis in this study uses data analysis techniques Miles and Huberman. Data analysis techniques are done by collecting, reducing, presenting, drawing conclusions. The results of the study show that the implementation of educative learning carried out by teachers through initial activities, core activities and closing activities in one sub theme of learning for four meetings is 62% of the criteria set. Based on the category on the multilevel scale the teacher's competency in the implementation of learning is at a poor interval.